THE MEDIATING ROLE OF FINANCIAL PERFORMANCE IN THE RELATIONSHIP BETWEEN ESG AND FIRM VALUE - Alif Desiana Silvi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Firm value is the condition of the firm that explains investors' views on the manager's performance in managing the firm. This research examines the mediating role of financial performance on the relationship between ESG and firm value. The population was taken from manufacturing companies listed on the Indonesia Stock Exchange (BEI) during 2020 - 2022. By using purposive sampling techniques, 111 observations were obtained. The data analysis technique used was multiple linear regression with STATA 15 software. The analysis results show that ESG has an insignificant negative effect on firm value, ESG has a significant positive effect on financial performance, and financial performance has a significant positive effect on firm value. However, financial performance does not mediate the relationship between ESG and firm value. Future research can expand the research object to other industries or replace financial performance proxies. Besides, the government is expected to encourage companies to implement and disclose ESG in annual reports, and investors can consider ESG information in their investment decisions.